2019
DOI: 10.1093/femspd/ftz022
|View full text |Cite
|
Sign up to set email alerts
|

Fosfomycin tromethamine activity on biofilm and intracellular bacterial communities produced by uropathogenic Escherichia coli isolated from patients with urinary tract infection

Abstract: Fosfomycin tromethamine (FT), an old antibiotic revived as a new strategy to overcome antibiotic resistance, is an excellent option for the treatment of lower urinary tract infection (UTI). During UTI, Escherichia coli produces biofilms and could invade the bladder epithelial cells, developing intracellular bacterial communities (IBC). The present work aimed to evaluate the activity of FT on biofilms and IBC from clinical isolates of E. coli. A total of 38 E. coli clinical UTI isolates previously characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 33 publications
0
8
0
1
Order By: Relevance
“…These results are surprising, as fosfomycin was shown to be a good antibiotic to treat biofilm, with a synergistic effect when it is associated with gentamicin [ 25 ]. In the context of urinary tract infections, a significant reduction in biofilm was reported for 38 tested clinical strains of E. coli [ 30 ]. However, in these two studies, fosfomycin was used against formed biofilms and was not investigated regarding its capacity to prevent biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
“…These results are surprising, as fosfomycin was shown to be a good antibiotic to treat biofilm, with a synergistic effect when it is associated with gentamicin [ 25 ]. In the context of urinary tract infections, a significant reduction in biofilm was reported for 38 tested clinical strains of E. coli [ 30 ]. However, in these two studies, fosfomycin was used against formed biofilms and was not investigated regarding its capacity to prevent biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
“…Fosfomycin is a broad-spectrum antibiotic that inhibits the formation of bacterial cell walls by competing with phosphoenolpyruvate transferase [ 11 ]. Bacterial resistance to fosfomycin is mainly attributed to chromosomes, and the cross-resistance between antibacterial agents such as beta-lactams and aminoglycosides is not significant [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most UPEC strains express type 1 fimbriae that facilitate the adhesion and colonization of UPEC by recognizing glycoproteins on the urinary tract epithelium [ 10 ]. The adhesion of FimH (type 1 fimbriae) induces the reorganization of the cytoskeleton and internalization of UPEC, which may protect the bacteria from antibiotics, neutrophil influx, and shear stress [ 11 ]. In addition to type 1 fimbriae, P fimbriae (composed of six subunits: papG, papF, papE, papK, papA, and papH ) recognize glycolipids (e.g., α -D-Gal-(1,4)- β -D-Gal) and interact with Toll-like receptor 4, inducing the local inflammatory response and promoting tissue destruction [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…UPECs persist in the urinary tract in different situations, such as IBCs or QIRs, and the ability to form biofilms on biological surfaces is a characteristic that may prevent bacteria eradication during antibiotic treatments [ 1 , 29 ]. Using a suitable in vitro model, it has been found that some cephalosporins, amikacin, and ciprofloxacin at concentrations similar to those achieved in human urine are able to reduce UPEC-produced biofilm [ 30 ].…”
Section: Antibiotics and Upecsmentioning
confidence: 99%